2018
DOI: 10.1111/cup.13393
|View full text |Cite
|
Sign up to set email alerts
|

High concordance of BRAF mutational status in matched primary and metastatic melanoma

Abstract: Background Techniques for the accurate identification of activating mutations of BRAF in metastatic melanoma are of great clinical importance, due to the availability of targeted therapies for these tumors. There is uncertainty regarding the frequency with which BRAF status differs between primary and metastatic sites. Methods Between 2011 and 2016, 219 melanoma cases underwent BRAF testing in our institution. In 53 of these cases, paired primary and metastatic specimens were available for polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…In our cohort, the concordance rates of BRAF, C-KIT, and NRAS mutations between paired primary and metastatic lesions were 94.0%, 97.7%, and 94.9% respectively. A recent study conducted by Cormican et al showed the high concordance of BRAF mutational status in matched primary and metastatic melanoma (52/53, 98%) 30 , which was higher than the results in our study. However, the study conducted by Manca et al revealed that mutational concordance in pathogenic/pathogenic like mutations between primary and metastatic melanoma was only 76% 6 , even different site from the same lesion could exist diverse genetic alterations [32][33][34] .…”
Section: Discussioncontrasting
confidence: 99%
“…In our cohort, the concordance rates of BRAF, C-KIT, and NRAS mutations between paired primary and metastatic lesions were 94.0%, 97.7%, and 94.9% respectively. A recent study conducted by Cormican et al showed the high concordance of BRAF mutational status in matched primary and metastatic melanoma (52/53, 98%) 30 , which was higher than the results in our study. However, the study conducted by Manca et al revealed that mutational concordance in pathogenic/pathogenic like mutations between primary and metastatic melanoma was only 76% 6 , even different site from the same lesion could exist diverse genetic alterations [32][33][34] .…”
Section: Discussioncontrasting
confidence: 99%
“…Several previous studies have described the heterogeneity of genetic alterations between primary and corresponding metastatic lesions in melanoma (19,(29)(30)(31). In our cohort, the concordance rates of BRAF, C-KIT, and NRAS mutations between paired primary and metastatic lesions were 94.0%, 97.7%, and 94.9%, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…In the metastatic setting, it is recommended to perform molecular analyses in metastatic sample, if available, because it represents the most recent lesion and it is often composed by a large majority of neoplastic cells. When a metastatic tissue sample is not available, the analyses may be performed on samples obtained from lymph node metastases or primary tumor since a high concordance of the BRAF status between primary melanomas and their metastatic lesions has been demonstrated (Colombino et al, 2012 ; Casula et al, 2016 ; Valachis and Ullenhag, 2017 ; Cormican et al, 2019 ; Pellegrini et al, 2020 ). Additionally, the NCCN clinical practice guidelines recommend BRAF mutation testing in patients with resectable and unresectable or metastatic melanoma to guide treatment decisions (NCCN Clinical Practice Guidelines in Oncology 3 )?…”
Section: Molecular Backgroundmentioning
confidence: 99%